Participation of the Catholic Student Association of the Republic of Indonesia in the Change of the Old Order – New Order - Andi Pandapotan Samosir (The International Journal of Politics and Sociology Research, 2022)
This study tries to describe the participation of the PMKRI organization in the change from the old order to the new order in Indonesia. The purpose of this study is to reveal the journey and struggles of student organizations, especially by PMKRI. Therefore, this thesis looks at how student organizations have a bargaining position in the transition from the old order to the new order. The researcher also saw the influence of the PKI which hegemonized in Indonesia, which was the biggest challenge at that time. Therefore, the researchers used the literature study and interview methods as data collection techniques and this research relied on the results of the analysis of library data and facts obtained from interviews with figures who played a role at that time. The data being discussed in this study are sourced from books, newspapers and the internet. The analytical method used in this study is a descriptive qualitative research method by describing, summarizing, and explaining various conditions with various variables that arise in the object of this research and revealing facts through data collection to be further studied, processed, analyzed and then concluded with descriptive way.